Improved microwave dielectric properties of novel low-permittivity Sn-doped Ca2HfSi4O12 ceramics. (September 2020) - Du, Kang; Song, Xiao-Qiang; Zou, Zheng-Yu; Fan, Jun; Lu, Wen-Zhong; Lei, Wen
Graphical abstract: Highlights: Novel low-permittivity Ca2 HfSi4 O12 microwave dielectric ceramic was investigated. Partial substitution of Sn 4+ for Hf 4+ could reduce εr value and improve Q×f value of Ca2 HfSi4 O12 ceramic. The τf value of Ca2 (Hf1- x Sn x )Si4 O12 ceramics could be controlled to near-zero by CaSnSiO5 second phase. The correlation between phase compositions and microwave dielectric properties of Ca2 (Hf1- x Sn x )Si4 O12 was investigated. Abstract: The phase compositions and microwave dielectric properties of Ca2 (Hf1- x Sn x )Si4 O12 (0 ≤ x ≤ 0.5) were investigated by the solid-state reaction method. A single-phase ceramic with monoclinic structure was formed in the Ca2 (Hf1- x Sn x )Si4 O12 (0 ≤ x ≤ 0.2) ceramic. At 0.25 ≤ x ≤ 0.5, CaSiO3 and CaSnSiO5 second phases appeared. The microwave dielectric properties of a novel Ca2 HfSi4 O12 ceramic ( ε r = 8.1, Q × f = 39, 700 GHz and τ f = ‒12.7 ppm/°C) were obtained. Partial substitution of Sn 4+ for Hf 4+ could reduce its relative permittivity and improve quality factor, and the highest quality factor of 49, 500 GHz was obtained at x  = 0.2. The τ f value of Ca2 (Hf1- x Sn x )Si4 O12 ceramics could be controlled to a near-zero value by the CaSnSiO5 second phase when x > 0.3. The optimum microwave dielectric properties ( ε r = 8.0, Q × f = 37, 100 GHz and τ f = ‒7.2 ppm/°C) were achieved in the Ca2 (Hf1- x Sn x )Si4 O12 ( x  = 0.4) ceramic.